Posers and Puzzles

Posers and Puzzles

  1. SubscriberAThousandYoung
    iViva la Hispanidad!
    tinyurl.com/y2c6j2t3
    Joined
    23 Aug '04
    Moves
    24791
    23 May '07 08:111 edit
    Why is this not incorrect?

    I wish I knew the right way to ask this Poser without giving it away...
  2. Joined
    29 Apr '05
    Moves
    827
    23 May '07 11:52
    if you have 1 infinity and remove 1 infinity, you still have 1 infinity. was it something like that?
  3. tinyurl.com/ywohm
    Joined
    01 May '07
    Moves
    27860
    24 May '07 00:50
    Originally posted by AThousandYoung
    Why is this not incorrect?

    I wish I knew the right way to ask this Poser without giving it away...
    Because it's correct.
  4. Standard memberagryson
    AGW Hitman
    http://xkcd.com/386/
    Joined
    23 Feb '07
    Moves
    7113
    24 May '07 20:22
    +1-1=1
    this goes to...
    +1-1-1=0 when you bring over the 1
    thus you're saying that -1=0 not good (the universe implodes or something)

    we could also try something crazy and rewrite it as...
    +1-(1=1)
    same as...
    1-1
    therefore =0
    function stands, though I think it's bad mathematical etiquette to have the brackets on either side of the equals sign, like a split infinitive.
  5. Pittsburgh, PA
    Joined
    03 May '07
    Moves
    1452
    24 May '07 22:19
    Originally posted by agryson
    +1-1=1
    this goes to...
    +1-1-1=0 when you bring over the 1
    thus you're saying that -1=0 not good (the universe implodes or something)

    we could also try something crazy and rewrite it as...
    +1-(1=1)
    same as...
    1-1
    therefore =0
    function stands, though I think it's bad mathematical etiquette to have the brackets on either side of the equals sign, like a split infinitive.
    in that case it's not a math problem. ()'s cannot start on the left side of = and end on the other.
  6. Standard memberagryson
    AGW Hitman
    http://xkcd.com/386/
    Joined
    23 Feb '07
    Moves
    7113
    25 May '07 06:13
    but it may not be a math problem, that's my point, from what I can see, it can only be true if we add things that aren't given (which is too arbitrary a problem) so I don't think it's simply maths.
  7. Standard memberagryson
    AGW Hitman
    http://xkcd.com/386/
    Joined
    23 Feb '07
    Moves
    7113
    25 May '07 06:16
    oh, and brackets can be on opposite sides of an = sign, it just prevents it from being an equation on its own. it's a messy way of abbreviating without having to resort to asides.
  8. Sigulda, Latvia
    Joined
    30 Aug '06
    Moves
    4048
    25 May '07 08:14
    Perhaps that's a result after a chess match. In that case +1-1=1 means that the player, who has this result, won one game, lost one and drew one.
  9. Joined
    14 Mar '06
    Moves
    3210
    25 May '07 14:10
    because +1 is the same as 1
  10. Joined
    21 Sep '05
    Moves
    75006
    25 May '07 16:35
    Originally posted by AThousandYoung
    Why is this not incorrect?
    Take the infinite series that starts +1 - 1 + 1 - 1 + 1 etc
    Obviously, +1 - 1 + 1 - 1 + 1 ... = +1 - 1 + 1 - 1 + 1 ...

    Now apply brackets:
    +1 - 1 + (1 - 1) + (1 - 1)... = +1 (- 1 + 1) (- 1 + 1) ...
    Each bracket is zero so this leave +1 - 1 = 1

    [You can also get to the same result through the more obviously flawed 0 = 1 'argument'. Then, if 0 = 1, it is obvious that +1 - 1 = 1.]
  11. SubscriberAThousandYoung
    iViva la Hispanidad!
    tinyurl.com/y2c6j2t3
    Joined
    23 Aug '04
    Moves
    24791
    30 May '07 09:27
    Originally posted by kbaumen
    Perhaps that's a result after a chess match. In that case +1-1=1 means that the player, who has this result, won one game, lost one and drew one.
    You got it, bud, or close enough. It's some GM's (I forget who) record against Fischer.
  12. Joined
    11 Nov '05
    Moves
    43938
    31 May '07 13:11
    -1 = 1
    Proof:
    -1 = sqr(-1)^2 = sqr(-1) * sqr(-1) = sqr(-1 * -1) = sqr(1) = 1
    Hence -1 = 1
  13. Sigulda, Latvia
    Joined
    30 Aug '06
    Moves
    4048
    31 May '07 14:42
    Originally posted by FabianFnas
    -1 = 1
    Proof:
    -1 = sqr(-1)^2 = sqr(-1) * sqr(-1) = sqr(-1 * -1) = sqr(1) = 1
    Hence -1 = 1
    i=-1^(1/2)
    -1=1
    sqrt(-1)=sqrt(1)
    i=1 hence
    1 = -1^(1/2)
Back to Top